Challenges and lessons learned from a long-term postauthorisation safety study programme of rivaroxaban in Europe - Luis Alberto García Rodríguez; Montse Soriano-Gabarró; Pareen Vora; Yanina Balabanova; Gunnar Brobert; Kiliana Suzart-Woischnik; Ana Ruigomez; Leif Friberg; Ron Herings; Karin M A Swart; Tania Schink; Elisabeth Smits; et al. (BMJ Open)
Objectives To describe opportunities and challenges experienced from the four pharmacoepidemiological database studies included in the rivaroxaban post authorisation safety study (PASS) programme and propose ways to maximise the value of population-based observational research when addressing regulatory requirements.Design PASS programme of rivaroxaban carried out as part of the regulatory postapproval commitment to the European Medicines Agency.Setting Clinical practice in Germany, the Netherlands, Sweden and the UK (electronic health records)—undertaken by pharmacoepidemiology research teams using country-specific databases with different coding structures.Participants 355 152 patients prescribed rivaroxaban and 338 199 patients prescribed vitamin K antagonists.Results Two major challenges that were encountered throughout the lengthy PASS programme were related to: (1) finalising country-tailored study designs before the extent of rivaroxaban uptake was known, and (2) new research questions that arose during the programme (eg, those relating to an evolving prescribing landscape).Recommendations We advocate the following strategies to help address these major challenges (should they arise in any future PASS): conducting studies based on a common data model that enable the same analytical tools to be applied when using different databases; maintaining early, clear, continuous communication with the regulator (including discussing the potential benefit of studying drug use as a precursor to planning a safety study); consideration of adaptive designs whenever uncertainty exists and following an initial period of data collection; and setting milestones for the review of study objectives.